Efficient interlayer charge release for high-performance layered thermoelectrics. Issue 2 (28th April 2020) - Zhu, Hao; Li, Zhou; Zhao, Chenxi; Li, Xingxing; Yang, Jinlong; Xiao, Chong; Xie, Yi
Abstract: Many layered superlattice materials intrinsically possess large Seebeck coefficient and low lattice thermal conductivity, but poor electrical conductivity because of the interlayer transport barrier for charges, which has become a stumbling block for achieving high thermoelectric performance. Herein, taking BiCuSeO superlattice as an example, it is demonstrated that efficient interlayer charge release can increase carrier concentration, thereby activating multiple Fermi pockets through Bi/Cu dual vacancies and Pb codoping. Experimental results reveal that the extrinsic charges, which are introduced by Pb and initially trapped in the charge-reservoir [Bi2 O2 ] 2+ sublayers, are effectively released into [Cu2 Se2 ] 2− sublayers via the channels bridged by Bi/Cu dual vacancies. This efficient interlayer charge release endows dual-vacancy- and Pb-codoped BiCuSeO with increased carrier concentration and electrical conductivity. Moreover, with increasing carrier concentration, the Fermi level is pushed down, activating multiple converged valence bands, which helps to maintain a relatively high Seebeck coefficient and yield an enhanced power factor. As a result, a high ZT value of ∼1.4 is achieved at 823 K in codoped Bi0.90 Pb0.06 Cu0.96 SeO, which is superior to that of pristine BiCuSeO and solely doped samples. The present findings provide prospective insights into the exploration of high-performance thermoelectric materials and the underlying transport physics. Abstract : Taking BiCuSeO as an example, we propose an efficient interlayer charge release strategy to optimize electrical transport properties in layered thermoelectrics by simultaneously providing charges and interlayer charge-transport channels.